Pengaruh Media Iklan Audio Visual Terhadap Kemampuan Menulis Teks Persuasi Pada Siswa Kelas VIII SMP Swasta Panca Jaya Galang - Nuriati Br. Lubis; Khairil Ansari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The aim of the research is to determine the superiority of students in writing persuasive texts before and after using audio-visual advertising media in class VIII of Panca Jaya Galang Private Middle School. This type of research is experimental research with Total Sampling techniques taken from two classes, namely VIII-A as the control class and class VIII-B as the experimental class with a total sample of 47 students. The data collection technique used was a description test. The data analysis technique used is quantitative analysis techniques, namely normality, homogeneity and hypothesis testing on variables, namely Audio Visual Advertising Media. The research output obtained from the experimental class and control class was 68.33 for the pre-test and 67.21 for the control class and 85.29 for the post-test mean and 77.47 for the control class. Data from the normality and homogeneity tests showed that the data were normally distributed and based on homogeneous data, namely the pre-test for the experimental class was normally distributed Lcount < Ltabel (0.08334 < 0.1798, the post-test was normally distributed because Lcount < Ltabel (0, 114339 < 0.1798), control class pre-test normally distributed Lcount < LTabel (0.098318 < 0.1798), post-test normally distributed because Lcount < LTabel (0.16621 < 0.1798). Hypothesis testing shows the results if the value of Sig (2-tailed) is 0.000 < 0.05, then the research hypothesis is accepted, namely that there is an influence of the use of audio-visual advertising media on the ability to write persuasive texts in class VIII students at Panca Jaya Galang Private Middle School.